Fatty infiltration of the pancreas: a systematic concept analysis - Mahyoub, Mueataz A.; Elhoumed, Mohamed; Maqul, Abdulfatah Hassan; Almezgagi, Maged; Abbas, Mustafa; Jiao, Yang; Wang, Jinhai; Alnaggar, Mohammed; Zhao, Ping; He, Shuixiang (Frontiers in Medicine, 2023)
Fatty infiltration of the pancreas (FIP) has been recognized for nearly a century, yet many aspects of this condition remain unclear. Regular literature reviews on the diagnosis, consequences, and management of FIP are crucial. This review article highlights the various disorders that FIP has been established as a risk factor for, such as type 2 diabetes mellitus (T2DM), pancreatitis, pancreatic fistula (PF), metabolic syndrome (MS), polycystic ovary syndrome (PCOS), and pancreatic duct adenocarcinoma (PDAC) and the new investigation tools. Given the interdisciplinary nature of FIP research, a broad range of healthcare specialists are involved. This review article covers key aspects of FIP, including nomenclature and definition of pancreatic fat infiltration, history and epidemiology, etiology and pathophysiology, clinical presentation and diagnosis, clinical consequences, and treatment. This review is presented in a detailed narrative format for accessibility to clinicians and medical students.